Clinical Features and Surgical Management of Intracranial Meningiomas in the Elderly - Naeem Ul Haq, Inayat Shah, Muhammad Ishaq, Musawer Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Given the threat related with surgical intervention of intracranial meningiomas in the older populace because of maturing physiology and numerous co morbidities, an endeavor was made to distinguish mediators impacting results and to characterize a category of individuals who ought not be surgically treated because of deprived prognosis. Study Setting: Mardan Medical Complex, KPK , PAKISTAN Material and Methods: The investigation of 58 individuals over the age of 70 years was conducted to determine short- and long-term results. Additionally, we derived scores for our patients using the previously reported CRGS, SKALE, and GSS grading systems. Result: The SKALE review technique indicated that only one important site was associated to neurological depression (P=0.02). Six people (10.3% of the total) quit due to their injuries. KPS 60 vs. KPS 70; P=0.0162); the American Society scale status (ASA 1 or 2 vs. ASA 3; P=0.0022); and the examination of meningiomas all had a link with death. Six occurrences of tumor recurrence were observed to be linked with the WHO grade (P = 0.00048) and the Simpson assessment of resection (P = 0.0437). In comparison to their Karnofsky score before surgery, the majority of patients either improved (50%) or did not change at all (24.9%). The 15.5% of patients who died as a result of the surgery or a recurrence are an exception to this rule. Conclusion: Neurological impairment following surgery was only observed in patients with a significant tumour placement (skull base, eloquent area, large vessels indulgence by the tumor). Because of the greatly increased threat of fatality, surgery should be carefully considered in individuals with a low functional state (KPS 60) or a bad bodily state (ASA 3 status). During routine visits, the majority of patients’ neurological health enhanced or remains constant in comparison to their condition before operation.